Creative arts in counseling and mental health - Neilsen, Philip, 1949-; King, Robert, 1949-; Baker, Felicity, 1970- (Los Angeles : SAGE, 2016)
Drawing on new paradigms and evidence-based discoveries in neuroscience, narrative psychology, and creativity theory, this text explores the beneficial role of expressive arts within a recovery perspective. A framework of practice principles for the visual arts, creative writing, music, drama, dance, and digital storytelling is addressed across a number of settings and populations, providing readers with an accessible overview of techniques taught in counseling programs in the U.S. and abroad.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Counseling; Psychotherapy; Arts -- Therapeutic use